(untitled) (American Journal of Islam and Society, 2002)
Dr. Mawil Izzi Dien, Senior Lecturer in Islamic Studies at the University of Wales, has been writing about Islam and environmental issues for almost two decades. The Environmental Dimensions of Islam is a summary of his previous writings presented together with new additions. Izzi Dien is one of the most prominent scholars in the new discourse of Islamic ecotheology, although he himself seldom refers to other Muslim scholars in this field, which somehow gives the wrong impression that he is the only one among Muslims dealing with environmental issues. After a short introductory chapter, Izzi Dien discusses in chapter 2 "The Environment and Its Components in Islam." This chapter gives an informative introduction to Qur’anic terminology on various environmental components and their status in Islam, such as water, earth, living organisms, diversity and biogeological cycles. This Qur’anic terminology is further developed in chapter 3, deaLing with theology pertaining to the environment. This chapter deals with issues such as the question of creation and the unseen and the Divine origin of everything: constancy, comprehensiveness, balance, and universal laws in nature as the Creation. I sympathize with much of the argument presented regarding the role of human beings in Creation, i.e., their trusteeship, partnership and responsibility. This chapter would have been strengthened by a discussion of the accusations from the environmental movement that the monotheistic religions represent an anthropocentric, and thus problematic, view of nature. For instance, the idea expressed in the Qur’an that God made nature subservient ????·akhkhara) to human beings may be criticized (see Qur’anic verses 2:29; 45:12-13; and 14:33-34), but the author chooses not to discuss this concept at all or to refer to other scholars’ criticisms. Another problem is his unusual definition of positivism, a philosophy held accountable for promoting a hegemonic position of science associated with a problematic view of nature. He sees positivism as something that Islam promotes, as in his view, it implies that human beings "are an active, positive force placed on this earth to construct, improve, and reform it." ln the Qur’an we read about examples of how people who destroyed their own habitat were punished by God in the form of ecocatastrophes ...